Better Fiscal Rules for a More Integrated EMU - Pierre Jaillet; Christian Pfister (Intereconomics, 2022)
The COVID-19 pandemic and the pressure it has created on member states' public finances have led European authorities to suspend the EU's fiscal rules. In fact, these rules had long been criticised by academics and had only been abided by exceptionally. Beyond the rules themselves, the lessons one can draw from the past 20 years also give good reason to revise the EU overall coordination framework.
Keywords: H60; H62; H63; 330